Inherent Optical Properties Attenuation Coefficient Modelling for Optical Shallow Water in Kepulauan Seribu of Jakarta, Indonesia - Setiawan, Kuncoro Teguh; Rosid, Mohammad Syamsu; Manessa, Masita Dwi Mandini; Suardana, A.A. Md. Ananda Putra; Adi, Novi Susetyo; Winarso, Gathot; Osawa, Takahiro; Asriningrum, Wikanti; Supardjo, Harsono (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Technology to obtain bathymetric information has become necessary considering the length of the coastline and the many islands owned by Indonesia. Measurement technology using multi-beam and single-beam echo sounders is still an alternative to producing bathymetric information. In shallow water, using echo sounders has constraints and limitations, such as being time-consuming, costly and prone to equipment damage. Remote sensing technology is an alternative to obtaining bathymetric information in shallow waters. Bathymetric modelling with analytical and semi-analytic models from satellites requires attenuation coefficients. Therefore, attenuation coefficient models are essential for satellite data. Attenuation coefficient studies using inherent optical properties (IOP) parameters have not yet been studied to determine Kepulauan Seribu bathymetry, Jakarta, Indonesia. The IOP modelling is determined by absorption and backscatter parameters. Chlorophyll-a Total influences these parameters: Total Suspended Matter (TSM) and Coloured Dissolved Organic Matter (CDOM). This study was performed to determine the attenuation coefficient model using multispectral remote sensing in the Kepulauan Seribu and applied five approaches to determining the attenuation coefficient via IOP: the Gordon, Kirk, Morel, Lee and Simon models. The five models' IOP attenuation coefficient results were compared to the in-situ attenuation coefficient value and evaluated. The results of IOP attenuation coefficient modeling of multispectral remote sensing based on the condition of local water parameters is Kd(λ) = 1.4369 ((a(λ) + b(λ)) / Cos θ) + 0.072. based on the modified Gordon method, The modelling results were obtained with an accuracy of 0.98 determination coefficient (R2) and 0.029 Root Mean Square Error (RMSE).